2021
DOI: 10.1126/science.abg8223
|View full text |Cite
|
Sign up to set email alerts
|

Free coherent evolution of a coupled atomic spin system initialized by electron scattering

Abstract: Full insight into the dynamics of a coupled quantum system depends on the ability to follow the effect of a local excitation in real-time. Here, we trace the free coherent evolution of a pair of coupled atomic spins by means of scanning tunneling microscopy. Rather than using microwave pulses, we use a direct-current pump-probe scheme to detect the local magnetization after a current-induced excitation performed on one of the spins. By making use of magnetic interaction with the probe tip, we are able to tune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 37 publications
1
49
0
Order By: Relevance
“…A recent experiment on spin-1/2 Ti atoms on 2ML MgO discovered that even a short current pulse (with less than one tunneling electron per pulse on average) is efficient at initializing the Ti spin under the tip (see section 2.7 and Ref. [33]). For higher-spin systems such as spin-5/2 Mn atoms on Cu 2 N, it was found that a low tunnel current can pump the Mn spin from |+5/2 to |+3/2 , while a very high tunnel current (that pumps faster than spin relaxations) can pull the Mn spin further up in the ladder, even reaching the highest |−5/2 state [62].…”
Section: Single Spin Initializationmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent experiment on spin-1/2 Ti atoms on 2ML MgO discovered that even a short current pulse (with less than one tunneling electron per pulse on average) is efficient at initializing the Ti spin under the tip (see section 2.7 and Ref. [33]). For higher-spin systems such as spin-5/2 Mn atoms on Cu 2 N, it was found that a low tunnel current can pump the Mn spin from |+5/2 to |+3/2 , while a very high tunnel current (that pumps faster than spin relaxations) can pull the Mn spin further up in the ladder, even reaching the highest |−5/2 state [62].…”
Section: Single Spin Initializationmentioning
confidence: 99%
“…These stringent requirements are met by drawing on powerful methodologies from material and quantum sciences, i.e., STM's abilities to build nanostructures atom-by-atom and selectively sense individual spin-carrying atoms, as well as ESR's ability to coherently control electron spin states via electromagnetic waves. This unique combination has so far enabled the quantum control of single electron spins of atoms [29,30,31,32,33] and molecules [34], as well as the manipulation of single nuclear spins through hyperfine interactions [35]. Quantum coherence can be increased using singlet-triplet states of a coupled spin system [36], allowing the observation of a free coherent evolution in the singlet-triplet basis [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RFSTM combines scanning probe microscopy with complementary concepts borrowed from microwave resonance spectroscopy, resulting in a powerful combination of high spatial resolution of m with simultaneous energy resolution of eV for spectroscopy. Recently, RFSTM methods have been developed that utilize an external modulation of the electric field across the tunnel junction at MHz to GHz frequencies; in particular, they have enabled the successful thermometry at the nanometer scale 4 , magnetic resonance spectroscopy at the single spin level 5 7 , noise spectroscopy 8 , addressing single-atom magnets 9 , 10 , ferromagnetic resonance 11 as well as spectroscopy of high-frequency mechanical motion of molecules 4 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…e direct manipulation and detection of individual spins (see Fig. 1(a)) is one of the major goals in contemporary nanoscience [1][2][3][4][5][6][7][8][9]. Meeting these challenges requires a local measurement of electronic and magnetic properties with atomic precision.…”
Section: Introductionmentioning
confidence: 99%